The Chinese version of the stigma of loneliness scale in people with chronic diseases: an assessment of psychometric characteristics - Zhiguang Fan; Xiaoli Shi; Yi Luo; Hongyan Chen; Hongjuan Wen (BMC Public Health)
Abstract Background Loneliness is prevalent in patients with chronic diseases and can threaten their health status, treatment process and quality of life. The stigma of loneliness stems from a derogatory and stigmatizing label that individuals possess towards loneliness with the possibility of being socially disadvantaged, which exacerbates the negative impact of loneliness on patients with chronic diseases and jeopardizes social support. However, few studies focused on this theme in patients with chronic diseases. This study aimed to assess the psychometric characteristics of the Chinese version of the Stigma of Loneliness Scale (SLS) among patients with chronic diseases, to provide a validated tool for related research. Methods The current study consisted of a two-phase questionnaire survey of 704 patients with chronic diseases. Sample 1 comprised 318 patients (Age:40.87 ± 18.55) with chronic diseases, and the data obtained were used for item analysis and exploratory factor analysis. Sample 2 included 386 patients (Age:40.65 ± 17.08) with chronic diseases, and the resulting data were of use for confirmatory factor analysis, criterion validity, incremental validity, and Cronbach’s α coefficient test. Moreover, in Sample 2, the equivalence of SLS in male and female cohorts and in outpatient and inpatient groups was further examined. Results In the exploratory factor analysis, two dimensions were extracted: Self-Stigma of Loneliness (SSL) and Public Stigma of Loneliness (PSL). The confirmatory factor analysis revealed that the first-order two-factor model demonstrated good fit indices (χ2/df = 2.754, RMSEA = 0.067, SRMR = 0.023, CFI = 0.988, IFI = 0.989, TLI = 0.983, PNFI = 0.677, PCFI = 0.681), and it was superior to both the one-factor model and the two-factor orthogonal model. The criterion validity test indicated that the SLS scores were significantly positively correlated with the scores of UCLA Loneliness Scale, Brief Illness Perception Questionnaire, Self-Concealment Scale, Social Interaction Anxiety Scale, Social Phobia Scale, Acceptance and Action Questionnaire-Second Edition, Kessler Psychological Distress Scale-6 scores. The Cronbach’s α coefficient values for the SLS, SSL, and PSL were 0.961, 0.949, and 0.960, respectively. The results of the incremental validity tests indicated that stigma of loneliness and loneliness differ in psychological construct. In addition, the SLS showed measurement equivalence in populations of patients with chronic diseases of different genders, as well as ways of seeking medical care. Conclusions The Chinese version of the SLS showed favorable reliability and validity in patients with chronic disease populations, which can provide instrumental endorsement for recognition and intervention studies of stigma of loneliness.